Der Heidi-Komplex: Gender, Feminismus und der Ekel vor der Gleichmacherei - Schutzbach, Franziska (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2016)
Since about 10 years we are experiencing a strengthening of conservative and right-wing parties and movements in Europe. Part of this development have been increasingly antifeminist politics: Constant attacks against feminist demands, activism and protagonists, while reclaiming traditional, biologistic familiy models and gender roles. More recently, the conservative targets have shifted from antifeminist assaults to a criticism of the concept of „gender“. This new form of attack does not argue against women’s rights or women’s equality, but rather against the so-called ideology of „genderism.“ They construe „genderism“ as a new dangerous ideology that – after the historical success of feminism – intends to destroy all gender-rules, including gender binaries and heteronormativity. The articles elaborates on this discursive shift.